Cleft Alveolar Bone Graft Materials: Literature Review. (March 2022) - Dissaux, Caroline; Ruffenach, Laetitia; Bruant-Rodier, Catherine; George, Daniel; Bodin, Frédéric; Rémond, Yves
Introduction: Since the early stages of alveolar bone grafting development, multiple types of materials have been used. Iliac cancellous bone graft (ICBG) remains the gold standard. Design/Methods: A review of literature is conducted in order to describe the different bone filling possibilities, autologous or not, and to assess their effectiveness compared to ICBG. This review focused on studies reporting volumetric assessment of the alveolar cleft graft result (by computed tomography scan or cone beam computed tomography). Results: Grafting materials fall into 3 types: autologous bone grafts, ICBG supplementary material, and bone substitutes. Among autologous materials, no study showed the superiority of any other bone origin over iliac cancellous bone. Yet ICBG gives inconsistent results and presents donor site morbidity. Concerning supplementary material, only 3 studies could show a benefit of adding platelet-rich fibrin (1 study) or platelet-rich plasma (2 studies) to ICBG, which remains controversial in most studies. There is a lack of 3-dimensional (3D) assessment in most articles concerning the use of scaffolds. Only one study showed graft improvement when adding acellular dermal matrix to ICBG. Looking at bone substitutes highlights failures among bioceramics alone, side-effects with bone morphogenetic protein-2 composite materials, and difficulties in cell therapy setup. Studies assessing cell therapy–based substitutes show comparable efficacy with ICBG but remain too few. Conclusion: This review highlights the lack of 3D assessments in the alveolar bone graft materials field. Nothing dethroned ICBG from its position as the gold standard treatment at this time.